The process of social adaptation towards climate change among Malaysian fishermen - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Md. Yassin, Sulaiman (Emerald Group Publishing, 2013)
Purpose: The purpose of this paper is to investigate the level of social adaptation to climate change among fishermen in the East Coast Region of Peninsular Malaysia. Design/methodology/approach: A set of questionnaires was developed based on the individual adaptive capacity framework on social adaptation to climate change developed by the International Union for Conservation of Nature and Natural Resources. Based on multi‐stage simple random sampling, a total of 300 registered fishermen in the East Coast Region of Peninsular Malaysia were chosen as the respondents. Findings: The fishermen surveyed had a high level of adaptation with regards to two aspects: first, environmental awareness, attitudes and beliefs; and second, local environmental knowledge. In contrast, they showed a low level of adaptation with regards to three aspects: attachment to place; formal and informal networks; and attachment to occupation. In addition, the fishermen had a moderate level of adaptation in relation to ten other aspects. Research limitations/implications: The findings of this study reflect social adaptation towards climate change among registered fishermen in the East Coast Region of Malaysia and results might be different if registered fishermen from other regions are included. Practical implications: The study demonstrated the strengths and weaknesses of the fishermen's adaptations to climate change. Such strengths and weaknesses have resulted in a number of suggestions and recommendations, which may work as tools by which to generate well‐planned and systematic adaptation options for dealing with the threatening impacts of climate change. Originality/value: Previous studies, both local and international, have consistently provided comprehensive explanatory reviews regarding climate change impacts on fishermen's activities. However, the common constraint of these studies is that aspects of adaptation are not under their radar; therefore, this study aims to fill this gap.